NEOREALISM AND DIGITAL TRANSFORMATION IN RUSSIA-UKRAINE WAR: A MORE CYNICAL PERSPECTIVE TOWARDS UNJUST WAR? - Syahdani, Muwalliha; Maharsi, Hayuningrum Citra; Zellatifanny, Cut Medika (Department of International Relations Universitas Satya Negara Indonesia, 2024)
The usage of digital technology, especially in warfare, on the one hand, exacerbates the judgment of the war. After the world experienced a major-devastating World War (I and II), International Relations – as a practice vis-à-vis discipline – has gone through a synthesis phase. Although the world has looked very different from the 19th century, states, as the acknowledged primary actors, are still chasing their national interests and power. Russia is one of the major powers after World War II, willing to reclaim its past glory by showing its possession towards the neighboring countries, one of which is Ukraine. This paper tries to judge the presence of digital technology as a combat equipment in worsening the magnitude of the war. This paper uses the International Humanitarian Law (IHL) as the principal guide for conducting a war. By contrast, what was happening in the field (das sein) will be seen through a Neorealism perspective as one of the major perspectives in International Relations studies. As the first full-scale modern cyber war, Russia-Ukraine has exemplified the use of digital technology to obscure the purposes of the war – creating a just and justified means to achieve national interest apart from political ways.